Managing Disequilibrium: A Grounded Theory Study of Therapists Working in Groups With People With Eating Disorders - Brinkman, Robyn (Auckland University of Technology, 2003)
This study has used a qualitative grounded theory research methodology to systematically identify what happens for therapists who facilitate groups for people with eating disorders. Eight therapists who had worked in groups with people with eating disorders were interviewed about their group experiences. A conceptual model of ‘managing disequilibrium’ emerged as the core concern of participants in this study, and this involved three stages. In the first stage therapists experienced shifting self-equilibrium during the group session that included a diverse range and intensity of experiences. In the second stage therapists subsequently engaged in a process of counterbalancing to manage disequilibrium while still in a group session. In the third stage therapists sought to re-establish equilibrium after a group session had ended. Therapists’ self-relationship, personal issues, clinical experience, and cognitive processes have been demonstrated to play a significant role in therapists’ management of disequilibrium; and strategies for in-group and post-group management have been described. Disequilibrium and countertransference have been compared and understood to bring different perspectives to therapists experiences in groups. Where countertransference emphasises theory and clinical practice, disequilibrium emphasises therapists’ subjective experiences and their instinctive need to compensate for difficult experiential phenomena during their clinical practice.
Keywords: Eating disorders; Eating Disorders -- therapy